Synchronous Leydig Cell Tumor and Seminoma in the Ipsilateral Testis - Ifeyinwa E. Obiorah; Alexandra Kyrillos; Metin Ozdemirli (Case Reports in Urology)
Leydig cell tumor is a rare sex cord tumor that accounts for 1–3% of all testicular neoplasms. Seminomas are more common and occur in 30–40% of testicular tumors. Leydig cell tumors are derived from undifferentiated gonadal mesenchyme and the concurrent development of the tumor and a seminoma which are derived from germinal epithelium in an ipsilateral testis is extremely rare. Here we report a case of ipsilateral Leydig cell tumor and seminoma occurring in a 38-year-old man with a left testicular mass. The key to diagnosis is dependent on histopathology and immunohistochemistry. To our knowledge, this is the first diagnosis of the two disease entities in a unilateral testis using immunohistochemistry. Increased awareness of the entity is important in order to distinguish Leydig cell tumor and seminomas from other malignancies due to difference in therapeutic management.